Two new Cincticostella species from China with a larval key to species of the genus (Ephemeroptera: Ephemerellidae) - Xie, Hui; Jia, Yan-Yan; Chen, Ping; Jacobus, Luke M.; Zhou, Chang-Fa (Zootaxa, 2009)
The larvae of Cincticostella bifurcata sp. nov. and C. szechuanensis sp. nov. have obvious and well-developed proand mesothoracic projections, which indicates that they belong to the ephemerellid genus Cincticostella. These larvae have unique characters within the genus. Cincticostella bifurcata sp. nov. has bifurcated abdominal tubercles on terga 5–8, and C. szechuanensis sp. nov. has no prominent, paired processes on the abdominal terga. The evolutionary trend of this genus is assumed to be a flattening and decrease in size of the body and a reduction or loss of the maxillary palpi. A key to all known larvae of the genus is provided.